CGIAR EiA climate adaptation prioritization tool - Alpha release - Steward, Peter; Rosenstock, Todd; Schmitter, Petra S.; Youngberg, Brayden; Achicanoy, Harold (2024)
Development version of CGIAR EiA Climate Adaptation Prioritization Tool